2013
DOI: 10.3892/mmr.2013.1791
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of ocotillol against doxorubicin-induced acute and chronic cardiac injury

Abstract: Abstract. Doxorubicin (Dox) has been clinically observed to exert marked anticancer activity. However, it is severely restricted by its associated dose-dependent cardiotoxicity, which may be attenuated by decreasing the cumulative dosage via combining with a non-toxic 'sensitizer'. We previously reported that ocotillol is capable of enhancing the antitumor activity of Dox; however, the effects of ocotillol on its cardiotoxicity remain unclear. In the current study, the effects of ocotillol on the toxicity of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…There were substantial evidences to show that ginseng had a wide range of pharmacological actions, including neuroprotective, cardioprotective, antioxidant and anticancer properties, in which the active ingredient were primarily thought to the ginsenosides14. Recently, we reported that Rh2 and ocotillol, two ingredients in the gingeng, attenuated doxorubicin-induced cardiotoxicology via their antioxidant capabilities1617. Here we reported that F1118, one pseudoginsenoside, attenuated the nephrotoxicity induced by CDDP without affecting its anti-tumor efficacy.…”
mentioning
confidence: 79%
“…There were substantial evidences to show that ginseng had a wide range of pharmacological actions, including neuroprotective, cardioprotective, antioxidant and anticancer properties, in which the active ingredient were primarily thought to the ginsenosides14. Recently, we reported that Rh2 and ocotillol, two ingredients in the gingeng, attenuated doxorubicin-induced cardiotoxicology via their antioxidant capabilities1617. Here we reported that F1118, one pseudoginsenoside, attenuated the nephrotoxicity induced by CDDP without affecting its anti-tumor efficacy.…”
mentioning
confidence: 79%
“…Ocotillol prevented depletion of glutathione and lipid peroxidation along with restoration of myocyte injury marker enzymes following preservation of cardiomyocytes cell membrane. Furthermore, ocotillol also improved cardiac function and hence was suggested as an adjuvant for counteracting DOX-induced cardiotoxicity [ 86 ].…”
Section: Phytochemicals Limiting Dox-induced Cardiotoxicitymentioning
confidence: 99%
“…18,28,29 The administration of Dox has been shown to cause toxicity and the depletion of leukocytes. 31,32 The results of the present study showed that free Dox induces both quantitative and qualitative changes in the leukocytes. The group of mice treated with free Dox exhibited a substantial reduction in leukocyte count compared to the groups injected with Lip-Dox or a combination of Lip-Dox and glycosphingosomes.…”
Section: Discussionmentioning
confidence: 73%